Non-spherical particle mixing behaviors by spherical inert particles assisted in a fluidized bed - An-Xing Ren (KeAi Communications Co., Ltd., 2019)
Abstract Fluidized beds are widely used in many industrial fields such as petroleum, chemical and energy. In actual industrial processes, spherical inert particles are typically added to the fluidized bed to promote fluidization of non-spherical particles. Understanding mixing behaviors of binary mixtures in a fluidized bed has specific significance for the design and optimization of related industrial processes. In this study, the computational fluid dynamic–discrete element method with the consideration of rolling friction was applied to evaluate the mixing behaviors of binary mixtures comprising spherocylindrical particles and spherical particles in a fluidized bed. The simulation results indicate that the differences between rotational particle velocities were higher than those of translational particle velocities for spherical and non-spherical particles when well mixed. Moreover, as the volume fraction of the spherocylindrical particles increases, translational and rotational granular temperatures gradually increase. In addition, the addition of the spherical particles makes the spherocylindrical particles preferably distributed in a vertical orientation.